Energy diagnosis of the company TEIMSA based on ISO 50001 - Miño Cascante, Gloria Elizabeth (2018)
In this research the production standards are formulated in direct correlation with the energy consumption, in this process the tools provided by the standard ISO 50001 are used to comply with the initiatives of improvement of the energy efficiency, optimization of the system of information management energy and auditing within the company “Textiles Industriales Ambateños” S. A. TEIMSA. By monitoring energy consumption, the efficiency of machines is determined, actions are taken regarding changes, improvements and projects that improve the company's metrics. As a result, we get to build the consumption baselines and set goals that allow us to manage an efficient management of energy resources through the application of measurable indicators of energy and validated by an expert judgment. Finally, it is concluded that the application of the first phase of the standard reflects the main subjects of energy consumption within the company and outlines the route for continuous improvement in the energy management of the company.